2022
DOI: 10.3390/app12178427
|View full text |Cite
|
Sign up to set email alerts
|

Using Chatbots as AI Conversational Partners in Language Learning

Abstract: Recent advances in Artificial Intelligence (AI) and machine learning have paved the way for the increasing adoption of chatbots in language learning. Research published to date has mostly focused on chatbot accuracy and chatbot–human communication from students’ or in-service teachers’ perspectives. This study aims to examine the knowledge, level of satisfaction and perceptions concerning the integration of conversational AI in language learning among future educators. In this mixed method research based on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Another vital theme derived from the analysis was the satisfaction of using chatbots for teaching and learning different language skills. Belda-Medina and Calvo-Ferrer (2022) investigated participants’ level of satisfaction employing the Chatbot–Human Interaction Satisfaction Model (CHISM) and found positive perception of the integration of conversational agents in language learning in terms of participants’ perceived ease of use (PeU) and attitudes (AT). In support of satisfaction, Hew et al (2022) found positive learner experiences concerning the chatbots’ perceived usefulness and ease of use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another vital theme derived from the analysis was the satisfaction of using chatbots for teaching and learning different language skills. Belda-Medina and Calvo-Ferrer (2022) investigated participants’ level of satisfaction employing the Chatbot–Human Interaction Satisfaction Model (CHISM) and found positive perception of the integration of conversational agents in language learning in terms of participants’ perceived ease of use (PeU) and attitudes (AT). In support of satisfaction, Hew et al (2022) found positive learner experiences concerning the chatbots’ perceived usefulness and ease of use.…”
Section: Resultsmentioning
confidence: 99%
“…Here, learners gain the necessary knowledge by taking advantage of every opportunity in a natural and realistic setting. As Chatbots are conversational agents, learners interact with others primarily through language, and conversation creates learning in the class and out of the class ( Adamopoulou and Moussiades, 2020 ; Belda-Medina and Calvo-Ferrer, 2022 ). The advantage of chatbots in education is improving the learning experience ( Okonkwo and Ade-Ibijola, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital-based foreign language teaching has been found to be effective in improving speaking skills. For example, research has shown that using digital language-learning software such as AI and chatbots can lead to gains in pronunciation, fluency, and vocabulary (Belda-Medina & Calvo-Ferrer, 2022 ). Additionally, the use of digital tools such as video conferencing and speech recognition software can provide learners with opportunities to practice their speaking skills in a simulated real-life context (Ranieri et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%